Processo avaliativo do estágio em Serviço Social na perspectiva dos supervisores de campo de uma instituição pública de ensino superior em Alagoas - Silva, Francinese Raquel Vieira (2019)
The Academic Course Completion Work (TACC) aimed to analyze the evaluation process of the internship in Social Work from the perspective of field supervisors. The methodology used was qualitative and exploratory, with the application of semi-structured questionnaire online (survey survey). The research results are presented in two original articles entitled: 1) The role of the field supervisor, in which data regarding the perception of the social worker in the role of supervisor are presented and 2) The evaluation of the internship in Social Work, in which present some considerations about the evaluation process of the internship from the perspective of health field supervisors. The first article presented as results: a team of field supervisors committed to the curriculum guidelines for the Social Work Course and aware of the learning objectives of the Supervised Internship discipline. About the role of the field supervisor, the commitment to the principle of unity between theory and practice was identified, as well as the role of directly accompanying, guiding and supervising the Social Work intern in order to insert him / her into the institution's daily life. Already the results found on the forms of assessment of the student learning process, focus of our second article, evidenced the requirement and appreciation of the summative assessment (with issuance of evaluation grade) by the Academic Training Unit (UFA) ), without excluding the formative dimension of this same process. Some examples of assessment tools were cited as the form offered by UFA, reports and other records such as portfolio, field diary, summaries and records, conversation wheels and trainee self-assessment (a). Regarding the ideal evaluation process, we can once again emphasize the democratic and participatory processes, as a way to favor student learning in line with the guidelines, principles and objectives that guide the pedagogical proposal of the internship. The results identified strengthen the critical reflection process of the field supervisor regardless of the area in which he is inserted. The study on the role of the supervisor and the evaluation exercise led to the development of two intervention products: 1) the holding of a workshop with the participants surveyed about the evaluation of the stage, as a way of giving feedback on the research data, including the review of the intern's evaluation form, 2) the elaboration of a manual with general guidelines for the internship, 3) social networking profiling and sharing of experiences and 4) website creation for socialization of internship guidance manual.